Efektifitas Pembelajaran Ilmu Alamiah Dasar yang Terintegrasi Dengan Al-Qur’an Melalui Modul Ajar Materi Tatasurya - Irdes Hidayana (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
The purpose of this research is to describe IAD learning using Al-Qur'an based modules. This research is quantitative descriptive. The results of the assessment of the implementation of IAD learning using Al-Qur'an based modules averaged the rating scale between 3.0 and 4.0 in the good category. The results of the percentage of implementation of class A is 89% with a reliability of 92% and class B is 93% with a reliability of 86%. The percentage of completeness of tarbiah faculty student learning outcomes in class A is 88.5% complete and 11.5% incomplete and in class B 96.4% complete and 3.6% incomplete. Students' positive response to IAD learning uses Qur'an-based modules. Based on the results of the study it can be concluded that learning IAD using Al-Qur'an based modules is said to be effective.